Estrategias metodológicas utilizadas por los docentes en el área de entorno natural y social, en el tercer año de educación básica de la escuela “24 de mayo” del cantón San Miguel, provincia Bolívar, en el periodo 2010 – 2011 - Bayas Romero, Edgar Lenín (2011)
The area of natural and social environment is essential for the formation of the deponent in the early years of basic education, because you can develop an understanding of social and natural world around him. For the same educational and methodological treatment is closely linked to the work of teachers and the implementation of methodological strategies to enable students to develop, cultivate and develop a set of skills that are useful to effectively participate in the teaching-learning process. Today more than ever are recognizing the value of education at lower levels, therefore the teachers are called to implement new challenges and directions in education, under these circumstances the subject of our research "Methodological Strategies used by teachers in the area Natural and Social Environment in the Third Year Basic Education School "May 24" the Canton San Miguel, Bolivar Province in the Period 2010-2011", provides an overview of the teaching work and the circumstances surrounding the educational process in this prestigious institution. The structure of work includes: the approach to the topic, problem, objectives, assumptions, it considers the treatment of theoretical underpinning research, complemented by field research developed by the educational institution itself, which showed results that support the development of the Learning Guide for the application of methodological strategies used by teachers. Moreover, the research addresses issues of concern, especially regarding the importance of the area of natural and social environment and with the proposal, which discloses a series of strategies that can be used to improve the level of meaningful learning for children and girls in the early years of elementary school.